Workforce diversity enhancing employee performance in small and medium-sized enterprises in Pakistan (Global Business Management Review (GBMR), 2022)
This study aimed to highlight workforce diversity in employee performance practice in Pakistan's small and medium enterprises. There is a significantly larger need for a diverse workforce in Pakistani SMEs because SMEs developing their positive contribution to sustaining a Pakistan economy and workforce diversifying the private sector in employment. The influence of diversity involves gender, age, education, and ethnic diversity to improve employee performance. This quantitative research used a survey method to collect data from 120 employees employed in SMEs in Pakistan. The study findings established the significant contribution of training for workforce diversity and employee performance is important for SMEs to solve work-related problems. Initially, employees need to understand the diverse system at SMEs for better team building to accomplish of a task. The statistical results also support the significant association of skills training and team building for task completion. The current study examines the significant challenges to workforce diversity top dimensions of gender, age, education, and ethnicity offer suggestions on how to improve workforce diversity and employee performance. This research is addressing workforce diversity and employee relations in small and medium-sized enterprises in Pakistan, and for better performance, SMEs in Pakistan must concentrate on giving staff tasks and training that are relevant to those tasks. The research influence that all the top four dimensions of workforce diversity (gender, age, education, ethnicity) have a positive correlation with employee performance in a Pakistani small-medium size enterprise. As a result, SMEs must operate workforce diversity to improve employee performance.